2017
DOI: 10.1016/j.addbeh.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative stress as a moderator of the effect of drinking motives on alcohol use and problems among young adults

Abstract: Background Research has demonstrated a strong relationship between drinking motives and alcohol use among young adult populations. Further, there is substantial evidence of the association between psychosocial stressors and greater alcohol consumption. In the present study, we examined whether acculturative stress would moderate the relationship between major drinking motives and alcohol use behaviors and alcohol-related problems, and whether this relationship differs by racial/ethnic group. Method Six hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
5
0
1
Order By: Relevance
“…Fourth, this meta-analysis did not allow for the examination of gender differences in the relation between drinking motives and drinking outcomes. 8 Finally, drinking motives do not exist in a psychological vacuum, and their effects are likely to be moderated by several psychological phenomena, including internalizing psychopathology (e.g., depression; Grazioli et al, 2018), personality traits (e.g., impulsivity; Mezquita et al, 2010), and other life stressors (e.g., acculturative stress; Conn et al, 2017). Further research should address the potentially interactive roles of these phenomena and establish whether the effect sizes consistently vary based on sample type (e.g., clinical vs. undergraduate sample).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Fourth, this meta-analysis did not allow for the examination of gender differences in the relation between drinking motives and drinking outcomes. 8 Finally, drinking motives do not exist in a psychological vacuum, and their effects are likely to be moderated by several psychological phenomena, including internalizing psychopathology (e.g., depression; Grazioli et al, 2018), personality traits (e.g., impulsivity; Mezquita et al, 2010), and other life stressors (e.g., acculturative stress; Conn et al, 2017). Further research should address the potentially interactive roles of these phenomena and establish whether the effect sizes consistently vary based on sample type (e.g., clinical vs. undergraduate sample).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The experience of acculturative stress is associated with a host of negative outcomes among Latinx such as anxiety and depression, and substance use including use of alcohol, specifically (Castillo et al, 2015; Crockett et al, 2007; Gil, Wagner, & Vega, 2000; Lui & Zamboanga, 2018; Zamboanga, Schwartz, Jarvis, & Van Tyne, 2009). For example, Hispanic/Latinx students reporting greater acculturative stress also report greater alcohol-related problems (Conn, Ejesi, & Foster, 2017). Yet, available work suggests that such relations may be complex and depend on a host of factors (e.g., age, place of birth; Gil et al, 2000).…”
Section: Acculturative Stress and Alcohol Use Among Latinxmentioning
confidence: 99%
“…Specially, we were interested in the associations of acculturative stress with IA. Previous studies have shown that acculturative stress has been widely linked to addictive behaviors and psychological well-being among international college students (Conn et al, 2017;Jin & Berge, 2015;Li et al, 2013). Thus, I hypothesized that acculturative stress would significantly predict IA while individual-level variables (i.e., age, gender, and length of stay) were held constant.…”
Section: Purpose Of the Present Studymentioning
confidence: 98%